2001
DOI: 10.1067/mtc.2001.113750
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of hospital size, case volume, and cost for coronary artery bypass surgery: Analysis of 12,774 patients operated on in Massachusetts during fiscal years 1995 and 1996

Abstract: Within the range of hospital size and case volume represented in this study, there is no evidence that either variable is related to the cost of performing coronary bypass surgery. Massachusetts hospitals appear to function on different segments of different average cost curves. It is not possible to predict the relative cost of coronary bypass grafting at a given hospital based primarily on volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…The multivariate analyses showed that nearly 40% of the variation in total New York State hospitalization charges could be explained on the basis of demographic, comorbidity factors, and between hospital variation, with an additional independent effect identifiable in the presence of an adverse drug effect to an antibiotic. The explained variance in the New York State hospitalization charges exceeds that observed in other published clinical predictor models of hospital charges based on statewide or province‐wide discharge databases 12, 20, 21. Although less variability was explained in national models, independent adverse drug effects influence on both total charge and length of stay were also observed.…”
Section: Discussionmentioning
confidence: 56%
“…The multivariate analyses showed that nearly 40% of the variation in total New York State hospitalization charges could be explained on the basis of demographic, comorbidity factors, and between hospital variation, with an additional independent effect identifiable in the presence of an adverse drug effect to an antibiotic. The explained variance in the New York State hospitalization charges exceeds that observed in other published clinical predictor models of hospital charges based on statewide or province‐wide discharge databases 12, 20, 21. Although less variability was explained in national models, independent adverse drug effects influence on both total charge and length of stay were also observed.…”
Section: Discussionmentioning
confidence: 56%
“…Although two studies found a negative association between volume and costs for PCI [11,12], one study of CABG found no association between volume and costs [13]. However, the latter study was based on only twelve hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have yielded contradictory evidence on whether high-volume facilities perform PCI and CABG at lower costs per patient. Some studies find substantial cost savings associated with high procedure volume [11,12]; while other research finds no evidence of a volume-cost relationship [13]. This disagreement may be due to the relatively small sample sizes and short time periods which were used to analyze the association between provider volume and costs.…”
Section: Introductionmentioning
confidence: 99%
“…Shahian et al (741) studied this question and found no relationship between either hospital size or annual CABG case volume and cost of performing bypass surgery. A major innovation has been the introduction of off-bypass CABG, which has reduced the postprocedure length of stay to between 2 and 3 days.…”
Section: Cost Reduction In Coronary Bypassmentioning
confidence: 99%